„Parki jutra” – idea parku w projektach architektów nowoczesności - Gielata, Ireneusz (Śląskie Studia Polonistyczne, 2018)
The article discusses the transformations of the idea of park in modernity. In the Age of Enlightenment Europe replaced the white of medieval cathedrals with the green of parks. A man, like Candide from Voltaire’s satire, started to “cultivate his garden,” changing private parks in public spaces. As a consequence of that process the idea of park as a place where you could experience beauty and pleasure completely “vanished”. Urban green spaces started to be determined by an efficacy parameter – which can be witnessed in Le Corbusier’s or Ebenezer Howard’s projects – thus opening the way for transforming former landscape parks into modern places of consumption: commercial parks and amusement parks.